Identification of osmoresponsive genes in Escherichia coli: evidence for participation of potassium and proline transport systems in osmoregulation. - Gowrishankar, J (1985)
Mu d1(Ap lac)-generated operon fusions were used in the identification of genes in Escherichia coli whose transcriptional expression is altered by changes in the osmolarity of the growth medium. One such osmoresponsive gene, designated osrA, was induced 400-fold when the osmolarity of the medium was increased with the addition of either ionic or neutral impermeable solutes but was not induced with glycerol, which is freely permeable across the cell membrane. osrA was mapped to 57.5 min and was shown to be transcribed clockwise on the E. coli chromosome. The ability of small concentrations of L-proline to promote the growth of E. coli in high-osmolar medium was shown to have been specifically lost in osrA mutants; other lines of evidence were also obtained to support the notion that osrA codes for an osmoresponsive L-proline transport system and is homologus to proU in Salmonella typhimurium. A second osmoresponsive operon identified was kdp, which codes for an inducible K+-transport system in E. coli. kdp expression was elevated 12-fold when the osmolarity of the growth medium was increased with the addition of impermeable ionic solutes but not neutral solutes; furthermore, osmoresponsivity of kdp expression was demonstrable only in K+-limiting media. kdp mutants were able to grow normally in high-osmolar media, but strains defective in both kdp and trkA (a gene for a second major K+-transport system) displayed an osmosensitive phenotype. The results suggest that transport systems for L-proline and K+, specified by osrA (proU) and kdp, respectively, play independent and important roles in osmoregulation in E. coli. A third osmoresponsive gene that was identified was lamB, which codes for an outer membrane protein for maltodextrin transport and lambda phage adsorption; its expression was reduced fourfold with increase in the osmolarity of the growth medium.